Analysis of newspaper content / Dr. Bukhory Ismail and Amelia Abdul Aziz - Ismail, Bukhory (Dr.); Abdul Aziz, Amelia (Faculty of Communication and Media Studies (FCMS), 1994)
Content analysis is used in this research. It is a method structured to analysed the content in a magazine, book or newspaper.